Keeping up with the Joneses and unemployment risk - Toche, P (University of Oxford, 2001)
This paper characterises the dynamic behaviour of a growing economy where individuals 'keep up with the Joneses' and face uninsurable labour income risk. Idiosyncratic uncertainty about future labour income reduces the marginal propensity to consume out of financial wealth and raises the effective rate of discount in the aggregate consumption Euler equation. The higher the average rate of income growth, the higher the saving rate. If individuals have uncertain lifetimes, a higher mortality rate reduces the marginal propensity to consume out of wealth, and raises the ratio of marginal utilities between employment and unemployment.